Banjir Kabupaten Sintang Tahun 2021 : Fakta dan Dampaknya Serta Kebijakan Mitigasi Bencana - Wida Novianti; Cau Kim Jiu (Journal of Educational Innovation and Public Health, 2024)
West Kalimantan has the longest river in Indonesia, namely the Kapuas River, where every year there is a potential for flood disaster in almost every district and city area that it passes through. The biggest flood in the last 20 years occurred in 2021, based on West Kalimantan BPBD data, 140,468 residents were affected by the flood and 2 residents were reported to have died in Sintang Regency. The flood disaster that occurred attracted enough public attention at the national level. The Central Government and its staff were also present to deal with the flood. The potential for similar floods is very likely to occur, requiring serious efforts to mitigate similar flood disasters from recurring. Method for preparing this article using a qualitative method with an exploratory approach. It is hoped that the results of this research can provide input in understanding conditions, dealing with them and making efforts to prevent and deal with similar flood disasters in Sintang Regency..